2015
DOI: 10.1007/s10620-015-3828-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Use of Antibiotics Is Associated with Colorectal Cancer Risk: Results of a Nested Case–Control Study

Abstract: BackgroundMicrobiotical dysbiosis induced by a Western diet seems to be associated with an increased risk of developing colorectal cancer (CRC). Few other factors with an effect on the colonic microbiota and their association with CRC have been evaluated.AimWe investigated whether the use of antibiotics is associated with CRC risk.MethodsData on the use of antibiotics and comedication were extracted from a health insurance database for subjects with a diagnostic-related group for CRC between 2006 and 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 34 publications
7
104
0
1
Order By: Relevance
“…37,38 The fecal microbiota from patients with CRC promoted tumorigenesis in germ-free or conventional mice given a carcinogen, 39 which showed the carcinogenic properties of the CRC microbiota. Accumulating epidemiological evidence supports the opinion that long-term antibiotic exposures, known to change the composition and decrease the diversity of gut microbiota, 40 increase the risk of CRC, [41][42][43][44] as well as gastric, pancreatic, lung, breast and prostate cancers. 45 Consistent with this, long-term antibiotic use was highly correlated with increased colorectal tumor progression in the Apc Min/+ mouse, a genetic model for human adenomatous polyposis.…”
Section: Gut Dysbiosis and Cancer Developmentmentioning
confidence: 90%
“…37,38 The fecal microbiota from patients with CRC promoted tumorigenesis in germ-free or conventional mice given a carcinogen, 39 which showed the carcinogenic properties of the CRC microbiota. Accumulating epidemiological evidence supports the opinion that long-term antibiotic exposures, known to change the composition and decrease the diversity of gut microbiota, 40 increase the risk of CRC, [41][42][43][44] as well as gastric, pancreatic, lung, breast and prostate cancers. 45 Consistent with this, long-term antibiotic use was highly correlated with increased colorectal tumor progression in the Apc Min/+ mouse, a genetic model for human adenomatous polyposis.…”
Section: Gut Dysbiosis and Cancer Developmentmentioning
confidence: 90%
“…Because a substantial fraction of ABx-treated patients shows an analogous rise in PA, it is highly probable that ABx treatment is not only associated 28 but indeed an independent risk factor for the development of chronic intestinal inflammation in IBD-susceptible individuals. It may be speculated that the high PA-mediated impairment of the large intestinal barrier might also play a role in the development of other chronic diseases that have been found to be associated with ABx therapies, such as irritable bowel syndrome22, 23 or colorectal cancer 25, 26. However, the pathophysiological impact of the rise in PA on the intestinal barrier in ABx-treated patients remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced abundance of these species might be a consequence of post-antibiotic dysbiosis. Supporting this assumption, a recent case-control study demonstrated an association between frequent use of antibiotics and the risk of CRC [81]. A cohort study including more than 3 million people could also demonstrate a relative risk of 1.37 (95% CI 1.34-1.40) of developing cancer and a risk of 1.15 (95% CI 1.04-1.26) of developing CRC in people who have had 6 antibiotic prescriptions or more in comparison to people with one prescription or less within the past 3 years [82].…”
Section: Antibiotics - Friend or Foe In The Pathogenesis And Course Omentioning
confidence: 98%